Positive Filtering with l1-Gain for Discrete-Time Positive Systems - Xiaoming Chen (Discrete Dynamics in Nature and Society)
This paper is concerned with the positive filtering problem for discrete-time positive systems under the l1-induced performance. We aim to propose a pair of positive filters with error-bounding features to estimate the output of positive systems. A novel characterization is first constructed so that the filtering error system is asymptotically stable with a prescribed l1-induced performance. Then, necessary and sufficient conditions for the existence of required filters are presented, and the obtained results are expressed as linear programming problems. Moreover, it is pointed out that the results can be easily checked by standard software. In addition, a numerical example is given to show the effectiveness of the proposed design procedures.